Problem of the heat radiative conductance in semitransparent media. The approximation of small reflection coefficient - Kolisnikov, A.V. (Functional Materials, 2007)
The stationary problem of the heat radiative conductance is solved at the so-called grey approximation in semitransparent media. Using the geometric optics approximation, the case of small coeficient 0 of the ray reflection from the sample boundary is investigated. The problem is solved in frameworks of perturbation theory on the reflection coefficient powers. At firs approximation, formulas of temperature stationary distribution are obtainded with asymptotic accuracy in the limit of large value of the material absorption coefficient.